Microplastic contamination in commercial sea salt of Vietnam - Ha, Dang Thi (Vietnam Journal of Science and Technology, 2021)
This is the first study which assessed the microplastic pollution of sea salt products from Vietnam. The results obtained from 9 iodate fine table sea salt and 4 raw sea salt samples collected from different regions in Vietnam showed that microplastic were present in 100% of the salts samples. The mean concentration of microplastic was 787±101 items/kg and 340±26 items/kg for raw and fine sea salts, respectively.  For both raw and fine sea salt, fibers were the predominant type of microplastic, accounted more 60% of total microplastic particles. In added, three types of polymer were detected in 12 microplastic particles by FTIR, including polyethylene (PE), polypropylene (PP) and polystyrene, in which, the most common is PE (accounted 67%). With a mean daily salt consumption of 5-10g/day, the annual number of microplastic particles ingested per Vietnamese adult varies from 637 to 1241 particles from salt alone.